Development of Glassy Bicontinuous Cubic Liquid Crystals for Solid Proton‐Conductive Materials. Issue 4 (24th November 2016) - Kobayashi, Tsubasa; Ichikawa, Takahiro; Kato, Takashi; Ohno, Hiroyuki
Abstract : Glassy bicontinuous cubic liquid crystals are developed to be a matrix having a hydrophilic infinite periodic minimal surface (IPMS). They function as a scaffold for water, leading to the formation of a 3D continuous hydrogen‐bonding network of water molecules along the IPMS. This material design is advantageous for developing novel electrolytes with rigidity and high proton conductivity.